IMMUNOLOGICAL INVESTIGATION OF TORQUE TENO VIRUS AMONG BLOOD DONORS IN MOSUL CITY, IRAQ - Anwer, Noor Sabah; Al-Taii, Hiyam Adil; Al-Taie , Anmar A. (PT. Antis International Publisher, 2025)
Objective: This study aimed to detect Torque Teno virus antigens using the ELISA technique and to evaluate the immune status by measuring the levels of inflammatory cytokines, namely Tumor Necrosis Factor (TNF) and Interleukin-10 (IL-10). Method: This study was conducted on 150 blood samples collected from blood donors at the main blood bank in Mosul, Iraq. The study used an enzyme-linked immunosorbent assay (ELISA) to detect viral antigens. The immune response was assessed by measuring the levels of tumor necrosis factor-alpha (TNF-α) and interleukin-10 (IL-10). Results: the ELISA test results revealed a low prevalence of TTV antigen (9.33%), with the highest rates recorded among the oldest age group (34–41 years) at 4.67%. Novelty: The results revealed the presence of immune regulatory dysfunction in this group of patients, as they exhibited signs of both immune activation and suppression simultaneously. This underscores the importance of continuous immunological monitoring for this category of patients.